Building trust during crises by engaging with existing distrust - Kattumana, Tarun; Larson, Heidi J. (Frontiers in Public Health, 2025)
It has often been argued that trust cannot be built during crises. While this line of thinking recognizes the importance of building trust before or after crises, it negates the possibility of building trust during a crisis. This paper offers two scenarios to argue for the possibilities of building trust during crises by engaging with existing distrust, with special reference to examples during the COVID-19 pandemic. The first considers distrust towards vaccines and public health interventions among Black Americans that was addressed through interventions that partnered with trusted third parties during the COVID-19 pandemic. The second discusses the Indian transgender community where trust networks built between public health organizations and activists groups was mobilized to engage with existing distrust during the COVID-19 pandemic. Despite the success of these interventions, this perspective paper ends by clarifying that engaging with distrust does not have to result in achieving public health goals with a brief considerations of two cases: the polio vaccine boycott in Nigeria (2003) and medical populism in the United States during the COVID-19 pandemic. These examples highlight that if existing distrust toward the medical system is not addressed, then space is created during crises-periods for distrust to be mobilized in ways that compromise public health goals.